Enrique Ayala Mora, Segundo Moreno Yánez, Guillermo Bustos, Rosemarie Terán Najas, Carlos Landázuri, Manual de Historia del Ecuador, 2 Vols., Quito, Universidad Andina Simón Bolívar, Sede Ecuador/Corporación Editora Nacional, 2008, 136 y 144 pp (Procesos. Revista Ecuatoriana de Historia, 2015)
s.r.